You must use the difference of squares formula: x2 - y2 = (x + y)(x - y) Thus: x2 - 25 = (x + 5)(x - 5).
x = ? 42 = x squared minus x
it is equal to +x
-25
(x - 5)(x + 4)
You have x+4=25 so you minus the four from four and you minus the four from the 25 . and then you get 21 so it is x=21
To solve the equation "x - 9 = 16," we need to isolate the variable x. Adding 9 to both sides of the equation, we get x = 16 + 9. Therefore, x = 25. So, 25 minus 9 equals 16.
40 - 25% = 40 x (1 - (25/100)) = 40 x 0.75 = 30
180 - 25% = 180 x (1 - (25/100)) = 180 x 0.75 = 135
24 - 25% = 24 x (1 - (25/100)) = 24 x 0.75 = 18
44 - 25% = 44 x (1 - (25/100)) = 44 x 0.75 = 33
35 - 25% = 35 x (1 - (25/100)) = 35 x 0.75 = 26.25
x(x - 25)(x - 25)
25 - (3 x 2) = 19
x is y plus 25% of y.
(x-5)(x+5)= x2-25
(x - 5)(x^2 + 5x + 25)